Potency and Test Sun Protection Factor (SPF) Preparation of Yellow Beetle Meat Extract Lotion (Cucurbita Moschata Durch.) As a Sunscreen - Lestari, Afnida Dwi; Nawangsari, Desy Nawangsari; Fitriana, Adita Silvia (Universitas Pekalongan, 2023)
Excessive exposure to ultraviolet radiation can cause skin damage. Products that can reduce the negative impacts of exposure to ultraviolet radiation include sunscreen. Pumpkin fruit (Cucurbita moschata Durch.) is a fruit that contains secondary metabolite compounds in the form of flavonoids to protect against sunlight. The aim of this research was to determine the SPF value, physical properties, and stability of the pumpkin extract (Cucurbita moschata Durch.) lotion formula. This lotion product is made in three different extract concentrations: 15%, 17.5%, and 20%. The research method used is laboratory-experimental. The research results show that the highest to lowest SPF values were obtained at F3, namely 8.274 (maximum protection), F2 7.898 (extra protection), and F1 7.401 (extra protection). The results of the physical properties show that the resulting lotion is homogeneous, thick in texture, pH in the range 6.4-6.9, viscosity in the range 3,263.9–7,177.2 cP, spreadability in the range 6.18–6.78 cm, and adhesive power in the range of 5.38–7.48 seconds. The results of the stability test of the lotion preparation showed a stable pH, unstable viscosity, stable adhesion to F2, and stable spreadability. The 6th cycle SPF test obtained F1 4,955 (medium protection), F2 5,184 (medium protection), and F3 6,473 (extra protection). The conclusion is that the highest SPF lotion is F3, namely 8.274 (maximum protection), homogeneous physical properties, pH 6.5, viscosity 7,177.2 cP, adhesion power 7.48 seconds, and spreadability 6.78 cm. The most stable stability test is at F2. The SPF value test in the 6th cycle produced a lower SPF value compared to the SPF value before the stability test was carried out